PENINGKATAN DAYA DUKUNG TANAH LEMPUNG PADA RUAS JALAN KERTAJAYA INDAH TIMUR SURABAYA DENGAN LUMPUR LAPINDO - Gati Sri Utami; Untung Usaha (Prosiding Seminar Nasional Sains dan Teknologi Terapan)
Heavy rainfalls have been known to be the cause of most of the slope failures in the world. It was suggested that the existence of cracks inside soils and slopes should be the main factors causing the slope to become very vulnerable under heavy to very heavy rain. Also, the easy draining condition along the cracks makes any type of slope to appear as behaving like sand when subjected to heavy rainfalls. The geotechnical engineering implications of this finding are, among others: much higher permeability values of soil in field, the Triaxial test results are no longer valid, special testing procedure is to be introduced for soil strength parameters, and much lower safety factors obtained for slopes than conventionally estimated. The remedial measures are somewhat suggested, such as installation of sub-drains system inside the slope, the use of ground anchor with high prestressing loads, and combinations with other soil reinforcement methods.